Retreatment with a pipeline embolization device for recanalized aneurysms following stent-assisted coiling embolization - Ling, Yuhui; Liu, Jie; Zhou, Liyun; Xiang, Xiuzhi; Wang, Peiming (Frontiers in Neurology, 2023)
Background and purpose Flow diverters have emerged as viable alternatives for the retreatment of recanalized aneurysms following stent-assisted coiling embolization. In this study, we aim to present our experience of retreatment for such aneurysms using the pipeline embolization device (PED). Materials and methods This case series presents a retrospective single-center analysis of patients with recanalized aneurysms who underwent retreatment using the PED between July 2019 and April 2023, subsequent to stent-assisted coiling embolization. Results The study includes five female patients, whose relevant clinical data were recorded. All patients had aneurysms located in the internal carotid artery, comprising two blood blister-like aneurysms and two giant aneurysms. Prior to the retreatment, two LVIS stents, two enterprise stents, and one solitaire stent were implanted. Among the five patients, one experienced a fatal post-operative subarachnoid hemorrhage, while two patients achieved complete embolization, and another patient achieved near-complete embolization during the last follow-up. Furthermore, one patient faced challenges during the placement of the PED and was unable to achieve successful deployment. We propose four overlapping relationships between a newly implanted PED and a previously deployed stent: (1) PED covering only the proximal end of the previous stent, (2) PED covering only the distal end of the previous stent, (3) PED covering both the proximal and distal ends of the previous stent, and (4) PED deployed within the previous stent. Antiplatelet therapy at our center involved daily dual therapy with aspirin (100 mg/day) and clopidogrel (75 mg/day) for at least 5 days before PED placement. Intra-arterial bolus administration of tirofiban (5 mcg/kg) was administered during or immediately after PED deployment, followed by a maintenance dose of 0.08 mcg/kg/min IV infusion for at least 24–48 h if necessary. Postprocedural dual antiplatelet therapy included clopidogrel (75 mg/day) for 6 months and aspirin (100 mg/day) for 12 months. Conclusion The findings of this study support the efficacy of the PED for the retreatment of recanalized aneurysms following stent-assisted coiling embolization.